1998
DOI: 10.1099/0022-1317-79-3-601
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral targeting indicates vagal spread of infection in hamsters fed with scrapie.

Abstract: The pathogenesis of scrapie and other transmissible spongiform encephalopathies (TSEs) following oral uptake of agent is still poorly understood and can best be studied in mice and hamsters. The experiments described here further extend the understanding of the pathways along which infection spreads from the periphery to the brain after an oral challenge with scrapie. Using TSE-specific amyloid protein (TSE-AP, also called PrP) as a marker for infectivity, immunohistochemical evidence suggested that the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(157 citation statements)
references
References 18 publications
(30 reference statements)
13
141
0
3
Order By: Relevance
“…Oral challenge of PrP Sc in rodents strongly suggested that infection spread from the gastrointestinal tract via the splanchnic and vagus nerves to the spinal cord and brain [2,3,15,22,23]. Recently, the same result was demonstrated in the cattle after an oral challenge of PrP Sc [12].…”
Section: Discussionsupporting
confidence: 59%
“…Oral challenge of PrP Sc in rodents strongly suggested that infection spread from the gastrointestinal tract via the splanchnic and vagus nerves to the spinal cord and brain [2,3,15,22,23]. Recently, the same result was demonstrated in the cattle after an oral challenge of PrP Sc [12].…”
Section: Discussionsupporting
confidence: 59%
“…Following up on experimental pathogenesis studies in mice (16)(17)(18)(19) and sheep (20), the animal model used in this study has provided key observations on the spread of infection through the body (4,(21)(22)(23)(24) that have been confirmed in naturally occurring ovine scrapie (25), field cases of BSE (26), orally transmitted BSE in primates (27), and orally transmitted or naturally occurring CWD (28,29). Additionally, more recent reports on the involvement of the sympathetic nervous system in vCJD (30) and the deposition of PrP Sc in muscles of patients with sporadic CJD (14) have shown the relevance of our hamster model for peripheral PrP Sc routing in TSE-affected humans.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with step-by-step infection of closely apposed cells, prions can multiply and spread along particular neuroanatomical pathways to reach the brain ( [9] and references therein). Extracellular forms of PrP Sc can also be detected in infected tissues [62], the diffusion of which could transmit infection to more distant cells [17].…”
Section: De Novo Infection and Cell-to-cell Dissemination Of Prionsmentioning
confidence: 78%